SIGNIFIKANSI DAN KONTRIBUSI PENDEKATAN SEJARAH DALAM STUDI ISLAM - Sri Endang Puji Astuti; Ubabuddin Ubabuddin (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The historical approach has become one of the most important and influential methods in understanding Islam as a religion, civilization, and socio-cultural phenomenon. The study in this research uses a literature research method. The results of the study indicate that the historical approach has several key contributions to the study of Islam. First, this approach allows a more nuanced understanding of the development of Islamic doctrine and practice over time. Second, the historical approach helps reveal the diversity of interpretations and expressions of Islam in various cultural contexts. Third, the historical perspective facilitates critical analysis of primary and secondary Islamic sources. The significance of the historical approach lies in its ability to bridge the gap between classical Islamic tradition and contemporary reality. This approach also contributes to the development of a more inclusive and interdisciplinary methodology in Islamic studies. In addition, historical understanding helps in addressing challenges such as religious extremism and tensions between Islam and modernity.